Moral philosophy from Montaigne to Kant - Schneewind, J. B. (Cambridge University Press, 2003)
This anthology contains excerpts from some thirty-two important seventeenth- and eighteenth-century moral philosophers. Including a substantial introduction and extensive bibliographies, the anthology facilitates the study and teaching of early modern moral philosophy in its crucial formative period. As well as well-known thinkers such as Hobbes, Hume, and Kant, there are excerpts from a wide range of philosophers never previously assembled in one text, such as Grotius, Pufendorf, Nicole, Clarke, Leibniz, Malebranche, Holbach and Paley. Originally issued as a two-volume edition in 1990, the anthology is now re-issued with a new foreword by Professor Schneewind, as a one-volume anthology to serve as a companion to his highly successful history of modern ethics, The Invention of Autonomy. The anthology provides many of the sources discussed in The Invention of Autonomy and taken together the two volumes will be an invaluable resource for the teaching of the history of modern moral philosophy.